The Reevaluation of Subgingival Calculus: A Narrative Review - Stephen K. Harrel; Atsutoshi Yoshimura; Charles M. Cobb (Dentistry Journal)
Aim: Despite a persistent presence in periodontitis, calculus remains a paradox. This narrative review reevaluates the role of calculus in periodontitis based on in situ, ex vivo, and in vitro studies published over the last two decades. Review: Results from multiple studies argue for the reconsideration of calculus as an independent risk factor in periodontitis. The results of a human study suggest that calculus contributes more to inflammation than simply serving as a substrate for biofilm accumulation. Ultrastructure studies have revealed residual calculus embedded in cementum following scaling and root planing (SRP). In vitro studies show that calculus particles can stimulate IL-1β secretion via the NLRP3 inflammasome in human and mouse phagocytes, and the crystalline structure is partially responsible for the activation. Other studies indicate that calculus particles may promote bone resorption via IL-1β induction in patients with periodontitis. Further, heat-treated calculus particles and hydroxyapatite crystals induce cell death in epithelial cell lines, suggesting that calculus plays a role in the breakdown of pocket epithelial integrity. Conclusions: Studies have shown that particles of microscopic calculus persist following traditional SRP. In vitro studies report that sterile and calcined calculus particles free of proteinaceous material are cytotoxic to cultured oral epithelial cells. Collectively, these studies suggest that residual microscopic calculus may be a potential risk factor for the failure of periodontal therapy.